The Videofluorographic Swallowing Study in Rheumatologic Diseases: A Comprehensive Review - Ambra Di Piazza; Federica Vernuccio; Massimo Costanzo; Laura Scopelliti; Dario Picone; Federico Midiri; Francesco Salvaggi; Francesco Cupido; Massimo Galia; Sergio Salerno; Antonio Lo Casto; Massimo Midiri; et al. (Gastroenterology Research and Practice)
Autoimmune connective tissue diseases are a heterogeneous group of pathologies that affect about 10% of world population with chronic evolution in 20%–80%. Inflammation in autoimmune diseases may lead to serious damage to other organs including the gastrointestinal tract. Gastrointestinal tract involvement in these patients may also due to both a direct action of antibodies against organs and pharmacological therapies. Dysphagia is one of the most important symptom, and it is caused by failure of the swallowing function and may lead to aspiration pneumonia, malnutrition, dehydration, weight loss, and airway obstruction. The videofluorographic swallowing study is a key diagnostic tool in the detection of swallowing disorders, allowing to make an early diagnosis and to reduce the risk of gastrointestinal and pulmonary complications. This technique helps to identify both functional and structural anomalies of the anatomic chain involved in swallowing function. The aim of this review is to systematically analyze the basis of the pathological involvement of the swallowing function for each rheumatological disease and to show the main features of the videofluorographic study that may be encountered in these patients.